2017
DOI: 10.1080/17425255.2017.1292252
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic considerations for cancer patients undergoing hemodialysis

Abstract: The increased incidence of cancer in hemodialysis patients has been discussed since the mid-70s. Today, physicians regularly encounter situations where they must manage the prescription of anticancer drugs in hemodialysis patients. Areas covered: Hemodialysis patients are at risk of dose-related toxicities due to pharmacokinetic modifications. Hemodialysis patients are at risk of therapeutic drug removal during their hemodialysis session, which may result in a loss of efficacy. In the advent of novel immunothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Indeed, only few cases were reported over times with no clear evidence of clinical outcomes [12,31]. As a consequence, it seems to be more a theoretical risk in thrombosis, but it is also important to consider the profile of the patients and more importantly the renal function and the nutrition status [32,33].…”
Section: Pharmacokinetic Ddis and Drug Transporter Ddismentioning
confidence: 99%
“…Indeed, only few cases were reported over times with no clear evidence of clinical outcomes [12,31]. As a consequence, it seems to be more a theoretical risk in thrombosis, but it is also important to consider the profile of the patients and more importantly the renal function and the nutrition status [32,33].…”
Section: Pharmacokinetic Ddis and Drug Transporter Ddismentioning
confidence: 99%
“…Khosravan et al [35] conducted a phase 1, single-dose study to study the PK of sunitinib at a dose of 50 mg and found that exposure of receptor tyrosine kinase inhibitor sunitinib was decreased in subjects that had end-stage renal disease potentially leading to lower efficacy. Janus and Launay-Vacher [36] have excellently reviewed elsewhere why clinicians need to be aware of the need to individualize treatment in hemodialysis patients who are increasingly being prescribed anticancer drugs.…”
Section: 0 Clinical Pharmacometrics For Cancer Precision Medicinementioning
confidence: 99%